2019
DOI: 10.1186/s12909-019-1560-8
|View full text |Cite
|
Sign up to set email alerts
|

Educating undergraduate occupational therapy and physiotherapy students in motivational interviewing: the student perspective

Abstract: Background Motivational Interviewing (MI) is an evidenced based talking therapy designed to affect client Health Behaviour Change. Previous research indicates that Allied Health Professionals (AHP) can effectively use the approach and training at pre-registration level has been piloted. However, student experiences of training is underexplored. Aim To explore Physiotherapy and Occupational Therapy students’ experiences of training in and implementation of Motivational I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Further to this, self-efficacy would likely be advanced more with access to actors and simulated practice environments [49]. The current study has demonstrated improvements are possible without the need for such enhancements and associated costs.…”
Section: The Need For Confidence In Communicationmentioning
confidence: 80%
“…Further to this, self-efficacy would likely be advanced more with access to actors and simulated practice environments [49]. The current study has demonstrated improvements are possible without the need for such enhancements and associated costs.…”
Section: The Need For Confidence In Communicationmentioning
confidence: 80%
“…Indeed, the transfer of learning to practice is complex, as evinced by Norris et al in an attempt to teach MI to undergraduate occupational therapy and physiotherapy stuents. 26 In a qualitative evaluation component of their study where they compared focus group results with student "post-it" notes in a post-training questionnaire, Norris et al uncovered two themes from the student perspective in regard to their learning: (1) desire to abide by the spirit of MI, and (2) facilitators and barriers to learning. The current study corroborated those findings wherein student reflections indicated a desire to perform better.…”
Section: Exploration Of Case Impactmentioning
confidence: 99%
“…Ability to understand the value of discussing such challenges is important when considering what support can be provided to students during the pandemic. Furthermore, the process of sharing difficulties will provide an opportunity to experience real play (Norris et al, 2019).…”
Section: Introductionmentioning
confidence: 99%